Additional fungal pathogens - Schwartz, Howard F. (International Center for Tropical Agriculture, 1989)
Bean plants are exposed to many fungal diseases including Alternaria leaf and pod spot, Ascochyta blight, ashy stem blight (Macrophomina phaseolina), Cercospora leaf spot, Chaetoseptoria leaf spot, Diaporthe pod blight, downy mildew (Phytophthora nicotianae var. parasitica and P. phaseoli), Entyloma leaf smut, floury leaf spot (Ramularia phaseoli), gray mold (Botrytis cinerea), gray leaf spot (Cercospora vandersysti), Phyllosticta leaf spot, powdery mildew (Erisiphe polygoni), scab (Elsinoe spp.), white leaf spot (Pseudocercosporella albida), and the yeast spot (Nematospora coryli). Infection may occur on seedlings or adult plants during the growing season or after harvesting. Some affect production slightly, but as cultural practices are modified, it may severely limit production in the future. The symptoms and damage caused by the diseases are illustrated in color. (CIAT)